Composition, structure and floristic diversity in dense rain forest in the Eastern Amazon, Amapá, Brazil (Acta Scientiarum. Biological Sciences, 2015)
This study aims to evaluate the phytosociology and floristic composition of tree species in the eastern Amazon, at the Iratapuru River Sustainable Development Reserve (RDS), State of Amapá. Fouteen quarters with dimensions of 100 m x 100 m were randomly inventoried, and 50 sub-plots of 10 m x 20 m were established. In each sub-plot all living individuals were sampled, being taken from the height data and DAP (breast height diameter) for tree species â‰¥ 10 cm. A total of 5,233 individuals belonging to 33 families and 184 species were registered. The families with the largest number of species were Fabaceae (32), Lauraceae (17), Sapotaceae (12), Moraceae (10), Lecythidaceae (8) and Annonaceae (8). The six most abundant families (18.18% of total families) in the present study were responsible for more than half (57.92%) of the total number of species. The floristic structure of the area studied was diverse, with species of varied interests, including: medicinal, timber and oil-producing.